Kecepatan Release Asam Salisilat dari Crosslinked Carrageenan Film : Pengaruh Konsentrasi Glutaraldehid sebagai Crosslinker - Steffy Devi Intan Permatasari Putri; Christine Melani; Sperisa Distantia (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2016)
Carrageenan which was extracted from seaweed Eucheuma cottonii has a potential to be modified into hydrogel. In this research, carrageenan was modified with a crosslinking method using glutaraldehyde as the crosslinker and the obtained film was applied to control the substance release rate, namely salicylic acid. The goal of this research was to determine the effect of glutaraldehyde concentration on the parameters of release rate of salicylic acid from the carrageenan film in buffer solution (pH=7,4). The carrageenan was crosslinked using glutaraldehyde solution (1-5%) using film immersion method and thermal curing at 110OC for 25 minutes. Salisilic acid was loaded in the film by immersing film in salisilic acid-aceton solution. The rate release of salisilic acid from crosslinked carrageenan film in buffer solution was determined  by measuring the concentration of salisilic acid  in various time of immersion. It was found that the mathematical model arranged could describe the mass transfer rate of salicylic acid release. The higher the concentration of glutaraldehyde, the consentration of salicylic acid in the film and the constant mass transfer rate tend to be lower, the range around 0,02/minute until 0,015/minute, while the equillibrium constant was higher, the range around 0,0842 until 0,1849 gram of solid/liter